Duch Remusa, Romulus i Lemuria. Publiusz Owidiusz Nazo, „Kalendarz poetycki” 5, 419–492 - Hartleb-Kropidło, Barbara (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
In the Remus’ story, Ovid presents to us the origin of the Lemuria festival and the version of early Rome history in which Romulus is not guilty of his brother’s death. The poet stresses Romulus’ pietas in his brother and creates a pattern of Augustus’ worship of his father Caesar and Mars, the ancestor of the entire Roman people.